A preliminary study of the mollusk locally known as imbaw I. characterization and determination of sexual dimorphism. - Sorongon, Ida Praile
The mollusk, locally known as "Imbaw" belonging to the family of Lucinidae refers to two species of bivalves, identified as Lucinoma annulata and Anodontia edentula under subfamily Myrteinae and Milthinae respectively. Each species has different morpholochical features as they differ in ridges, shell lenght, width, height, ligament or attachment of both valves and color of periostracum. Internally they differ in gonad color and size. In both species, sexes are separate although little differences can be observed in shell structure to distinguish the female from the male. Gonadal somatic index was found to be greater in females.